1992
DOI: 10.1038/sj.bdj.4807966
|View full text |Cite
|
Sign up to set email alerts
|

The structure and function of the temporomandibular joint

Abstract: Although characterised by having a synovial membrane lining the nonarticulating surfaces within the joint capsule, in some ways the temporomandibular joint (TMJ) is an atypical joint. This paper highlights the differences between the TMJ and other movable joints with a description of the structure, innervation blood supply and musculature. Also included are details of how the TMJ moves--the effectors of movement and the various reflexes controlling movement of the joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 0 publications
0
21
0
2
Order By: Relevance
“…(1976). Others authors have reported a few chondroid cells in different phases of adult life (Bellinger, 1948;Castellaneta, 1950;Macalister, 1954;Choukas & Sicher, 1960;Mckay, Yemm & Cadden, 1992).…”
Section: Resultsmentioning
confidence: 95%
“…(1976). Others authors have reported a few chondroid cells in different phases of adult life (Bellinger, 1948;Castellaneta, 1950;Macalister, 1954;Choukas & Sicher, 1960;Mckay, Yemm & Cadden, 1992).…”
Section: Resultsmentioning
confidence: 95%
“…With these characteristics, the disc can be in tight contact with the articular surfaces of condyle and fossa during joint movements, which is important for maintaining normal TMJ function. 12,13 Kurita et al 14 reported that a frequently found characteristic of TMJ discs that had been surgically removed from TMD patients was that they were thicker than normal. An increased thickness may reflect a change in functional demand or may be the result of pathology.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 As the mouth is opened, the mandibular condyle rotates within the glenoid fossa and then glides forward onto the articular eminence. Measurement of the range of mandibular condyle movement provides mean values of 19.4 mm in men and 18.2 mm in women.…”
Section: Operative Techniquementioning
confidence: 99%